Sintesis GO/C-Dots Berbahan Dasar Limbah Batang Tembakau Dengan Liquid Sonication ‎Exfoliation Dan Metode Pemanasan Oven - Sabrina Tsaqilatussyifa; Rizka Ekawati; Ahmad Muntako; Firdaus; Deni Aryati; Asmida Herawati (Postgraduate, University of Mataram, 2025)
This study investigated the utilization of tobacco stem waste as a green precursor for the synthesis of GO, C-Dots, and GO/C-Dots composites with 1:1 and 1:3 ratios through oven drying methods and liquid sonication exfoliation (LSE). Characterization techniques, including UV-Vis-NIR spectroscopy, XRD, FTIR spectroscopy, SEM, PL, and TRPL, were used to evaluate the synthesized materials. The GO/C-Dots composites exhibited an energy band that classifies them as organic semiconductors. XRD analysis showed a change in crystallinity and indicated an increase in C-Dots content. FTIR analysis showed a shift in functional groups at 1:1 to 1:3 ratios that showed an inverse trend. SEM analysis showed that the addition of C-Dots significantly affected the surface morphology and elemental composition of GO. TRPL test showed consistent results with the trend of PL intensity where C-Dots had the highest value and GO the lowest. This finding highlights the potential of GO/C-Dots composites as sustainable materials, with further exploration needed to assess their applications in various fields such as optoelectronics, catalysis, and environmental science.